SUMOylation of VEGFR2 regulates its intracellular trafficking and pathological angiogenesis - Zhou, Huanjiao Jenny; Xu, Zhe; Wang, Zongren; Zhang, Haifeng; Zhuang, Zhen W.; Simons, Michael; Min, Wang (Nature communications, 2018)
Regulation of VEGFR2 represents an important mechanism for the control of angiogenesis. VEGFR2 activity can be regulated by post-translational modifications such as ubiquitination and acetylation. However, whether VEGFR2 can be regulated by SUMOylation has not been investigated. Here we show that endothelial-specific deletion of the SUMO endopeptidase SENP1 reduces pathological angiogenesis and tissue repair during hindlimb ischemia, and VEGF-induced angiogenesis in the cornea, retina, and ear. SENP1-deficient endothelial cells show increased SUMOylation of VEGFR2 and impaired VEGFR2 signalling. SUMOylation at lysine 1270 retains VEGFR2 in the Golgi and reduces its surface expression, attenuating VEGFR2-dependent signalling. Moreover, we find that SENP1 is downregulated and VEGFR2 hyper-SUMOylated in diabetic settings and that expression of a non-SUMOylated form of VEGFR2 rescues angiogenic defects in diabetic mice. These results show that VEGFR2 is regulated by deSUMOylation during pathological angiogenesis, and propose SENP1 as a potential therapeutic target for the treatment of diabetes-associated angiogenesis. VEGFR2 is a central regulator of angiogenesis. Here Zhou et al. report that SUMOylation of VEGFR2 regulates its subcellular localisation and activity, and that endothelial-specific knockout of the SUMO endopeptidase SENP1 protects against VEGFR2-mediated pathological angiogenesis.